A Comprehensive Investigation of Associations of Objective and Subjective Socioeconomic Status with Perceived Health and Subjective Well-Being. Issue 1 (3rd June 2020) - Kezer, Murat; Cemalcilar, Zeynep
Socioeconomic status (SES) accounts for disparities in health and well-being. Recent studies consider the effects of individuals' subjective standing in society (i.e., subjective SES) as well as the traditional (objective) indicators of SES (i.e., income, education, occupational status), in predominantly Western samples. This study presents a comprehensive investigation of associations of objective and subjective SES with individuals' perceived health and well-being in a representative sample of young adults (aged 18–35; N = 3016) from a non-WEIRD (Western, Educated, Industrialized, Rich and Democratic) population (i.e., Turkey), employing polynomial regressions and plotting the results onto a three-dimensional plane. Findings confirmed the value of polynomial regression to understanding the relationship of different types of SES with perceived health and well-being. For instance, while perceived overall health was descriptively greater when objective-SES exceeded subjective-SES, the reverse was the case for happiness, one indicator of well-being. Our findings also suggest an additive effect of the two types of socioeconomic status on majority of the outcome variables; individuals' perceptions of overall health, life satisfaction, happiness, and financial satisfaction were enhanced when they reported higher scores on both objective and subjective SES.